Bilayer Tablet: Montelukast Sodium Nanoparticles with Sustained Release Mesalamine for Ulcerative Colitis - Subramanian Somaskandan, (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Oral drug administration is highly preferred for its ease and patient compliance, with tablets and capsules leading the market. Bilayer tablets, composed of two layers, support targeted delivery by different layer releases at different sites and allow for easy identification. Targeted colonic drug delivery is particularly effective for conditions like ulcerative colitis, enhancing drug concentration at the site while minimizing side effects. Techniques such as ionic gelation and the use of pH-sensitive polymers like Eudragit are key to achieving controlled release, specifically in the colon. Materials and Methods: The montelukast sodium nanoparticles were done by implementing ionic gelation method using chitosan a biocompatible polymer, sodium tripolyphosphate as a negative inorganic compound to cross-link the chitosan and to produce nanoparticles. The prepared solution undergoes homogenization at 35,000 rpm for 5 min and sonication for 10 min and then subjected to lyophilization. The nanoparticles were evaluated for particle size, zeta potential, entrapment efficiency, and scanning electron microscopy. Dry granulation method was used to prepare another portion of bilayer tablet, mesalamine sustained release (SR) portion with the addition of polymer Eudragit L100 and S100 on the ratios of F1 (2.5:2.5), F2 (2:3), F3 (3:2), F4 (4:1) and F5 (1:4), excipients such as magnesium stearate as lubricant, talc as glidant and sodium starch glycolate as a disintegrant. After the compression of each layer sequentially (mesalamine SR and montelukast nanoparticles), bilayer tablet was formed which then evaluated for weight variation, friability, hardness, thickness, disintegration time, in vitro dissolution profile, and release kinetics model. Results and Discussion: Among five formulations of bilayer tablets, F5 (1:4) (Eudragit L100: Eudragit S100) formulation is considered as better due to its increased drug content of mesalamine was 98.12% and montelukast sodium was 96.3%, in vitro dissolution study of montelukast sodium followed first order kinetics with 98.7% drug release and mesalamine was 82.16% release with zero order kinetics. Conclusion: The single bilayer tablet proves the suitability of sustained-release mesalamine and immediate-release montelukast for a better approach in ulcerative colitis.